Mapping Aquifer Zones in the Terai Region of Nepal Using the Natural Electromagnetic Field Technique: A Case Study from Rajbiraj Municipality, Saptari - Pandey, Nirab; Shrestha, Birat; Shrestha, Arun; Pandey, Sanjeeb; Pandey, Nishant; Sharma, Gaurav (Journal of Nepal Hydrogeological Association, 2025)
This research paper demonstrates the application of the Natural Electromagnetic Field Frequency Selection System (specifically the PQWT-TC150 instrument) for mapping aquifer units in the Terai region of Nepal. The electromagnetic method, utilizing very low frequency (VLF) signals (0–30 kHz), was employed to delineate groundwater-bearing zones through resistivity contrasts in Quaternary alluvial sediments of Rajbiraj Municipality, Saptari District. Three survey profiles identified low-resistivity anomalies indicative of productive saturated formations below 15 m depth. This aquifer depth can be correlated with the nearby borehole and results from the existing literatures. Based on the lithological composition and hydrogeological characteristics, the present study area lies in the transition zone between the Bhabar Zone and Middle Terai. The Bhabar Zone characterized by coarse, permeable sediments has low (seasonal) drainage density, as it facilitates rapid groundwater recharge, whereas the Middle Terai has dense drainage network as the river gains water in this region, due to presence of fine-grained sediments, promoting higher storage capacity but slow flow rates. This quick non-invasive technique offers significant socio-economic benefits as it reduces costs and risks associated with drilling. It aids to prevent financial losses caused by unsuccessful drilling. This saves time and resources.